2017
DOI: 10.1371/journal.pone.0185467
|View full text |Cite
|
Sign up to set email alerts
|

Previous uterine artery embolization increases the rate of repeat embolization in a subsequent pregnancy

Abstract: This study aimed to determine the rate of repeat uterine artery embolization (UAE) in women with a previous UAE. Study data were collected from the Korea National Health Insurance Claims Database of the Health Insurance Review and Assessment Service for 2009–2013. We enrolled women who had a first delivery in 2009 and a second delivery between 2010 and 2013. Among 226,408 women who had a first delivery in 2009, 296 underwent UAE. A total of 127,506 women had a second delivery between 2010 and 2013. Of 296 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…13,[19][20][21][22][23] The study reported by Cho et al included 96 women and represents the largest study of subsequent pregnancy after UAE due to PPH. 32 A multivariate-adjusted analysis showed that UAE during a first delivery increased the rate of UAE at a second delivery (0.10% vs 5.9%; odds ratio, 25.56; 95% CI, 9.86-66.23), but the authors did not investigate the causes of PPH or the PAS rates; thus, the study did not satisfy our criteria for inclusion in the literature review.…”
Section: Discussionmentioning
confidence: 98%
“…13,[19][20][21][22][23] The study reported by Cho et al included 96 women and represents the largest study of subsequent pregnancy after UAE due to PPH. 32 A multivariate-adjusted analysis showed that UAE during a first delivery increased the rate of UAE at a second delivery (0.10% vs 5.9%; odds ratio, 25.56; 95% CI, 9.86-66.23), but the authors did not investigate the causes of PPH or the PAS rates; thus, the study did not satisfy our criteria for inclusion in the literature review.…”
Section: Discussionmentioning
confidence: 98%
“…A less invasive alternative to surgical methods is the UAE. The UAE has a success rate of 90% for adequate hemostasis . The UAE enables identification of the bleeding site easily and does not require laparatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The UAE has a success rate of 90% for adequate hemostasis. 19 The UAE enables identification of the bleeding site easily and does not require laparatomy. One of the disadvantages is the absorption of embolization substance which may cause repeat embolizations and extravasations.…”
Section: Discussionmentioning
confidence: 99%